Peningkatan Ekonomi Paska-Pandemi Melalui Pengembangan Ulat Hongkong pada Kelompok Masyarakat Pembudidaya Ikan Air Tawar “Sumber Duren” Kabupaten Malang: Enhanching Post-Pandemic Economic Recovery Through the Development of Mealworm Cultivation in Community Group of “Sumber Duren”, Freshwater Fish Cultivator, Malang Regency - Nursyam, Happy; Yufidasari, Hefti Salis; Astuti, Retno Tri; Setijawati, Dwi; Meitasari, Deny; Septian, Wike Andre; Hussein, Naufal Amirudin; Ash-Syufi, Abdillah Hanan; Septiansyah, Farhan Amar; Kuntowibisono, Eduardus; Raihannisa, Widi; Putra, Azriel Zharif Adha Ekta; Febriansyah, Zulfikri; Dharma, Syahrizal Bima Satya; Sembiring, Dariyus DC (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Senggreng Village is one of the areas in Sumber Pucung District, Malang Regency, promising to be developed in agriculture, animal husbandry, fisheries, and agro-tourism. Abundant water resources mainly support the fisheries and agriculture potency due to its position near the Sutami Dam. One of the community groups in Senggreng Village,